The death of the animal in South African history (Historia, 2021)
Never before in human history have so many animals been subjected to horrific slaughter, unconscionable abuse, and unthinkable living conditions These conditions have a unique history that requires both material and philosophical analysis, and it is a history that needs to be attended to in its specificity so that we might learn better how to transform it. 1 Thus Matthew Calarco in his contribution to Paola Cavalieri's collection, The Death of the Animal (2009). Running through the conversations comprising this book is a thread of dissention at the Socratic, rationalistic approach taken by analytic philosophy to the question of rights for animals.
Keywords: rights for animals; horrific slaughter; unconscionable abuse